Effect of intravenous administration of 20% Mannitol on optic nerve sheath diameter in patients with raised intracranial pressure - Poudel, Shiva; Rimal, Ankit; Shrestha, Ninadini; Gurung, Arjun; Shrestha, Anil (Journal of Nepalese Society of Critical Care Medicine, 2023)
Background and aims: Mannitol is commonly used to reduce elevated intracranial pressure (ICP) in patients with traumatic brain injury, intracranial hemorrhage and acute cerebrovascular accident. Optic nerve sheath diameter (ONSD) has high sensitivity and specificity in diagnosing raised ICP. This study aims to evaluate effect of Mannitol on ONSD in patients with raised ICP. Methods: This was a prospective cohort observational study of adult patients receiving osmotherapy for increased ICP admitted to the ICU. Baseline ONSD (T1) was recorded bilaterally followed by administration of Mannitol. ONSD was remeasured bilaterally at 30 (T2), 60 (T3) and 120 (T4) minutes after completion of administration of mannitol. Peak inspiratory pressures and PEEP were recorded for patients on mechanical ventilation. Results: Of the 40 patients included in the study, the mean age of patients was 54.03 ±19.15 years. Among them 26 were mechanically ventilated. Compared to the baseline values of 6.1 ± 0.74 mm, the mean ONSDs at T2, T3 and T4 were significantly lower after administration of 20% Mannitol with all p values < 0.001. A statistically significant correlation between change in ONSD (ΔONSD) at each time point and the dose of Mannitol administered was observed. Conclusion: ONSD can be used for monitoring effectiveness of osmotherapy on a point-of-care basis in patients with elevated ICP.